Relações étnico-raciais na escola: relato de professores - Silva, Janaína de Oliveira (Universidade Federal de São Carlos, 2020)
In the current context, talking about Ethnic-Racial Relations at school has great relevance, considering the school as an environment that forms possible social or reproductive changes in today's society. The present research started with the following questions: "What are the experiences of those interviewed with the theme in the classroom as students and teachers? What are the contributions of educational laws that aim to implement education for ethnic-racial relations from early childhood education?", seeking to present the relevance of addressing the issue in the educational sphere and the contributions that they can bring to the school community, having an impact on society as a whole and considering the teacher as a major character in this process. The research is anchored in the qualitative approach, based on authors such as Demarzo (2009), Fernandes (1972), Munanga (2003), Gomes (2002), among others, seeking to know from a semi-structured interview with four teachers from Sorocaba and region, from public and private schools, their practices in the classroom and identify the contributions of educational laws, such as the amendment of LDB 11.645/08, which point to the insertion of the theme since early childhood. The results obtained point to the need to have in the teacher's own formation the specific subject of ethnic-racial relations, in order to base future teachers on the knowledge of Africa and its peoples, of our history and cultures. This will contribute to a better understanding of the students, the school as a whole and society about who we are, generating an antirracist education capable of transforming the Brazilian reality more egalitarian.
Ethnic-racial relations at school: teachers' report
Keywords: Relações Étnico-Raciais. Cultura. Racismo. Formação de professores. Respeito.; Ethnic-Racial Relations. Culture. Racism. Teacher training. Respect.; CIENCIAS HUMANAS::EDUCACAO